Study on adhesion formation and the healing of colon anastomosis in rats with induced peritoneal sepsis - Silva,Silvana Marques e (2011)
PURPOSE: To evaluate the effects of abdominal sepsis on adhesion formation and colon anastomosis healing in rats. METHODS: Forty rats were distributed in two groups containing 20 rats each for left colon anastomosis in the presence (Group S) or absence (Group N) of induced sepsis by cecal ligation and puncture. Each group was divided into subgroups for euthanasia on the third (N3 and S3) or seventh (N7 or S7) post-operative day. The amount of adhesions was evaluated and a segment of the colon was removed for histopathologic analysis, bursting strength assessment, hydroxyproline and the determination of tissue collagen. RESULTS: The subjects which underwent cecal ligation and puncture presented a higher amount of intra-abdominal adherences in both third (p=0,00) and seventh (p=0,00) post-operatory days. Smaller bursting strengths were found in the S3 subgroup, and greater bursting strengths were found in the S7 subgroup. There was no difference in the variations on the concentrations of hydroxyproline, tissue collagen and histopathology. CONCLUSIONS: The peritoneal infection which was developed by cecal ligation and puncture raised the amount of intra-cavitary adhesions. There was a decrease in the amount of colonic anastomosis on the third post-operatory day with a following raise on the seventh without any effects on other healing parameters.